Human papillomavirus infection plays a role in conjunctival squamous cell carcinoma: a systematic review and meta‐analysis of observational studies. Issue 5 (16th November 2020) - Ramberg, Ingvild; Møller‐Hansen, Michael; Toft, Peter Bjerre; Funding, Mikkel; Heegaard, Steffen
Abstract: Purpose: We aimed to study the prevalence of human papillomavirus (HPV) in conjunctival intraepithelial neoplasia and carcinoma. Furthermore, we aimed to explore whether geographical differences or different detection modalities are associated with the conflicting information regarding HPV and the development of the disease. Methods: We searched the MEDLINE, EMBASE and Scopus databases for studies reporting on HPV and conjunctival intraepithelial neoplasia or carcinoma. The pooled prevalence proportions, odds ratio (OR) and corresponding 95% confidence intervals were calculated assuming a random‐effects model. Subgroup analyses and meta‐regression explored possible sources of heterogeneity. Results: A total of 39 studies were included in the systematic review. The pooled prevalence of HPV in conjunctival intraepithelial neoplasia and carcinoma was 26%, with HPV16, 18, and 33 being the most frequently reported genotypes. Human papillomavirus (HPV) infection was associated with an increased risk of conjunctival intraepithelial neoplasia and carcinoma (OR 8.4, 95% confidence interval (CI) 3.7–19.1); lower in studies from African countries (OR 1.7, 95% CI 0.9–3.5) than other countries (OR 16.1, 95% CI 5.8–44.3), p = 0.013. Conclusion: Human papillomavirus infection increases the odds of conjunctival intraepithelial neoplasia and carcinoma by 8.4 compared to healthy conjunctival mucosa or other ocular surface diseases. There seem to be geographical differences regarding HPV in conjunctival intraepithelial neoplasia and carcinoma. HPV16 was the most prevalent genotype, followed by HPV18 and HPV33, meaning that most of the HPV‐related conjunctival intraepithelial neoplasia and carcinoma may be prevented by the HPV vaccines that are currently available.